Price Theory - Weyl, E. Glen (Journal of Economic Literature, 2019)
I argue that there exists a coherent and relevant tradition in economic thought that I label “price theory.” I define it as neoclassical microeconomic analysis that reduces rich and often incompletely specified models into “prices” (approximately) sufficient to characterize solutions to simple allocative problems. I illustrate this definition by highlighting distinctively price theoretic approaches to prominent research practices (diagrams and problems sets) and substantive research topics (e.g. selection markets and media slant). I trace the origins of price theory from the early nineteenth century through its segregation into the Chicago School in the last quarter of the twentieth. I argue that price theory plays a valuable complementary role to two traditions, “reductionism” and “empiricism,” with which I contrast it and show how this contribution of price theory has fueled a resurgence in this style of research in fields ranging from market design to international trade. Approximations critical to price theory are less formally developed than tools used in other methodological traditions, suggesting a research agenda to clarify the accuracy and range of validity of these methods.(JEL B13, B21, B41, D00, D47, F10)